EFL Learners’ Feedback on The Use of Short Movies in English Speaking Classroom - Angraini, Nike (LPPM Universitas Bina Sarana Informatika, 2025)
Abstract –Current investigation was intended to see the feedback of EFL learners on the application of short movies in English speaking classroom. Experimental research design was consciously chosen which primarily concerned on descriptive statistical analysis. Fourteen sample was taken purposefully. To measure the EFL learners’ feedback, distribution of questionnaire items set was utilized. Twenty one items were designed to seek the aspects of psychological, linguistics, and literature. The findings revealed that positive feedback were made by the participants viewed from psychological viewpoint (English learning preference, motivation, enthusiasm, and bravery). In addition, positive feedback were also earned by majority of the EFL learners on their English speaking aspects seen from linguistics viewpoint (pronunciation, vocabulary, content, grammar, and fluency), excluding intonation. Besides, positive feedback were possessed by some other EFL learners concerned on literature viewpoint (generating moral lesson, understanding sequence of movie events, speaking and writing, as well as analyzing movie event), excluding story plot. Some following parties limited to English lecturers, EFL students, stakeholders, and other researchers were offered several pedagogical implication.